1997
DOI: 10.1074/jbc.272.11.7132
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Is a Transcriptional Modulator That Communicates with Transcription Factor IIB and the RNA Polymerase II Subunit 5

Abstract: Hepatitis B virus X protein (HBx) transactivates viral and cellular genes through a wide variety of cis-elements. However, the mechanism is still obscure. Our finding that HBx directly interacts with RNA polymerase II subunit 5 (RPB5), a common subunit of RNA polymerases, implies that HBx directly modulates the function of RNA polymerase (Cheong, J. H., Yi, M., Lin, Y., and Murakami, S. (1995) EMBO J. 14, 142-150). In this context, we examined the possibility that HBx and RPB5 interact with other general trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
174
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(180 citation statements)
references
References 63 publications
5
174
0
Order By: Relevance
“…49 At the level of promoter function, transient expression of HBV genetic information in HepG2 cells has been used to evaluate the ability of various cytokines alone and in combination to alter the function of the HBV core/pregenome promoter, 47 to study the functional interaction of specific transactivation factors and cellular binding proteins with elements within the X promoter, 42 and to demonstrate that HBV X protein may facilitate transcriptional initiation of cellular and viral genes by stabilizing the association between RNA polymerase and TFIIB. 43 The HBV baculovirus infected HepG2 cell system described in the current study represents a new method for using HepG2 cells to study HBV. Indeed, the HBV baculovirus system, like 2.2.15 cells, can be used to evaluate the effect of nucleosides, cytokines, and/or novel drugs on HBV replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49 At the level of promoter function, transient expression of HBV genetic information in HepG2 cells has been used to evaluate the ability of various cytokines alone and in combination to alter the function of the HBV core/pregenome promoter, 47 to study the functional interaction of specific transactivation factors and cellular binding proteins with elements within the X promoter, 42 and to demonstrate that HBV X protein may facilitate transcriptional initiation of cellular and viral genes by stabilizing the association between RNA polymerase and TFIIB. 43 The HBV baculovirus infected HepG2 cell system described in the current study represents a new method for using HepG2 cells to study HBV. Indeed, the HBV baculovirus system, like 2.2.15 cells, can be used to evaluate the effect of nucleosides, cytokines, and/or novel drugs on HBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…14,[40][41][42][43][44][45][46][47][48][49] In this study, we report the development of a novel transient mechanism for studying HBV in the well differentiated human hepatoblastoma cell line HepG2. We conclude the following from our studies:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,45 HBx has been shown to possess a dual function, acting at both the nuclear and the cytoplasmic compartments. 46 The nuclear function of HBx appears to be mediated by the physical association of HBx with proteins of the transcriptional machinery 47,48 and with certain transcription factors such as CREB/ATF. 6 The cytoplasmic function of HBx involves the activation of the Ras/Raf/ ERK 49,50 and the MEKK-1/JNK 50 signalling cascades, which in turn are implicated in the activation of certain transcription factors such as AP-1 and NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…7 Few studies also showed that transcriptional transactivator protein X encoded by the human hepatitis virus may specifically interact with RPB5 to stimulate transcription in virally infected cells. 5 with these specific partners do not account for the fact that RPB5 is shared by all 3 yeast RNAPs. 2,10 Earlier studies also proved the close relation of human RPB5 to the archaeal subunit H. 11 and to viral RPB5-like subunits.…”
Section: Introductionmentioning
confidence: 99%